Surveying the Academic Literature on the Use of OKR (Objective and Key Results) - Silva, Roberto Vasconcelos; Souza, Gleison Dos Santos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
Context: OKR (Objective and Key Results) has emerged as a lightweight framework for business objectives measurement and strategic alignment. Problem: Although we may observe a growing interest in OKR in the industry, the academic literature on OKR still needs to be explored. Solution: We aim to identify how and why OKR has been used by researchers and information technology (IT) organizations while capturing associated difficulties, benefits, and lessons learned. IS Theory: This work is conducted under the General Systems Theory, focusing on understanding how IT organizations and individuals (i.e., researchers) deal with using or adopting a measurement method. Method: We executed a systematic mapping study surveying Engineering Village, Scopus, IEEE Xplore, Web of Knowledge, SpringerLink, ScienceDirect, and Wiley digital databases and complemented the results with snowballing. Summary of Results: We found 30 studies mentioning OKR and its use. Most studies (23 out of 30) were published after 2020. In general, OKR use is under-documented from a theoretical point of view. Most selected studies present little or no information on why or how OKR was used. Among the topics associated with using OKR are communication, performance evaluation, tasks planning and prioritization, transparency, team alignment, and goal fulfillment. Contributions and Impact in the IS area: This study revealed few academic studies addressing the topic. Some research questions, such as lessons learned and difficulties in implementation, still need more answers. Also missing are details on how OKR is implemented. Nonetheless, we captured information regarding the main benefits and advantages of using OKR. We expect this work will provide relevant content for other researchers.